Mishnah and the Social Formation of the Early Rabbinic Guild : a Socio-Rhetorical Approach. - Lightstone, Jack N. (Wilfrid Laurier University Press, 2006)
Where do the origins of the rabbinic movement lie, and how might evidence from the early rabbinic literature be made to reveal those origins? In order to shed light on the early social formation of the rabbinic guild of masters, Lightstone brings the theoretical and methodological insights of socio-rhetorical analysis to examine Mishnah, the first document authored by the early rabbinic movement and its principal object of study for several centuries. He argues that the enshrinement of Mishnah served to model, via its pervasive rhetoric, the principal authoritative guild expertise that qu.